"Mater celeberr. Mozart" - Morgenstern, Anja; Neumayr, Eva (Vienna Hollitzer, 2023)
Maria Anna Mozart, the mother of the Mozart siblings and wife of Leopold Mozart, is often described as uneducated, unsociable and not even musical. Many biographers of Wolfgang Amadé Mozart agree that he inherited his talent from his father and his tendency to use faecal language from his mother.To mark the 300th anniversary of her birth, Anna Maria Mozart, née Pertl (1720-1778) is at the centre of a new book for the first time. Published by Hollitzer-Verlag in Vienna, the symposium volume mater celeberr. Mozart. Anna Maria Mozart on her 300th birthday, edited by Anja Morgenstern and Eva Neumayr, contributions by Mirijam Beier, Christoph Großpietsch, Monika Kammerlander, Anja Morgenstern, Eva Neumayr, Wolfgang Neuper and Käthe Springer-Dissman deal with her biography, her education, her depiction in pictures and her reception in the Mozart biography of the mother of the Mozart siblings.In addition, the important social role of musicians‘ mothers in the 18th century will be discussed on the basis of selected biographies that shed light on the cultural activities of women in musicians’ families, thereby also revealing new aspects of Anna Maria Mozart's life and work. The results presented here suggest that Anna Maria Mozart had a stronger influence on the development of her famous son Wolfgang Amadé than previously assumed.
Includes bibliographical references (pages 200--225) and index.
Keywords: Mozart, Anna Maria -- 1720-1778; Mozart, Wolfgang Amadeus -- 1756-1791; Mozart family; Biography; History